THE INFLUENCE OF ANIMATED VIDEO MEDIA ON ADOLESCENTS’ KNOWLEDGE LEVEL ABOUT HIV/AIDS AT SMK ISTIQOMAH MUHAMMADIYAH 4 SAMARINDA - Valentina, Widya; Tripertiwi, Sucita; Sulistyorini, Chandra; Wahyuni, Ridha (HEARTY, 2025)
HIV/AIDS in adolescents not only has a negative physical impact, but can also affect mental health, emotions, economic status, and long-term social well-being. One of the factors influencing adolescent behavior is their low level of knowledge about reproductive health and their tendency to try new things. Efforts to reduce the incidence of HIV/AIDS in adolescents require integrated and comprehensive handling. One way is by providing education. Research Objective: To analyze the effect of animated video media-based health education on increasing adolescent knowledge about HIV/AIDS. Method: This study used a Quasi-experimental design with a One Group Pre-test and Post-test. The research was conducted in May 2025, with the population being all 10th-grade students of SMK Istiqomah Muhammadiyah 4 Samarinda. The sample consisted of 109 people. The type and data collection method was primary data using a questionnaire sheet. The statistical test used was the Wilcoxon test. Research Results: There was an effect between knowledge before and after health education using animated videos with a p-value <0.001. Conclusion: There was an effect of increased respondent knowledge after health education with animated video media on the level of adolescent knowledge about HIV/AIDS at SMK Istiqomah Muhammadiyah 4 Samarinda. Suggestion: Adolescents are expected to be able to access information and health services about HIV/AIDS from various information sources.